Symptomatic facial nerve canal meningocele: A rare cause of recurrent meningitis and facial nerve palsy - Timothy Tynan; James Bowman; Chris Que Hee; Gareth Lloyd (Otolaryngology Case Reports, 2021)
A symptomatic facial canal meningocele is a rare entity which poses a diagnostic dilemma for otologists, neurosurgeons and neuroradiologists. Computed tomography (CT) and magnetic resonance imaging (MRI) can assist with the diagnosis. Treatment options range from conservative management with interval imaging to surgical management, which must balance the risk of post-operative facial nerve paralysis. The preferred operative management in refractory meningitis cases, due to CSF leak, involves subtotal petrosectomy and blind sac closure. This report presents a case of child with a background of a Type 1 Arnold-Chiari malformation, who presented with a prolonged history over 8 years with presentations of recurrent meningitis, facial nerve palsy and unilateral sensorineural hearing loss. The unusual diagnosis of a facial nerve canal meningocele was made and subsequenently underwent a tympanomastoidectomy/subtotal petrosectomy and blind sac closure.